Studying The Temurid Heritage in The Activities of I.M. Muminov (Zien Journal of Social Sciences and Humanities, 2022)
The history of Amir Temur has always been in the center of attention not only of historians, but also of many statesmen and politicians. Particular attention is paid to the military art of Temur, which is studied in military academies and higher educational institutions. But in the Soviet period, the history of Amir Temur was revealed one-sidedly, the negative sides with large excesses were revealed, the true advantages of the state of Sahibkiran were obscured. In 1968, Academician I. Muminov's book "The Role and Place of Amir Temur in the History of Central Asia" was published, which caused a great resonance in the public life of the country. This article reveals the spiritual feat of the scientist - academician I. Muminov, who undertook the rehabilitation of the activities of Amir Temur at the peak of the rampant communist ideology.